2017
DOI: 10.1186/s12885-017-3468-1
|View full text |Cite
|
Sign up to set email alerts
|

ALK-rearranged lung squamous cell carcinoma responding to alectinib: a case report and review of the literature

Abstract: BackgroundAlthough anaplastic lymphoma kinase (ALK) fusion genes are generally identified in lung adenocarcinoma patients, they are relatively rare in patients with squamous cell carcinoma (SqCC). Metastatic ALK-rearranged lung adenocarcinoma patients treated with ALK inhibitors demonstrate higher response rates, improved progression-free survival, and reduced toxicity relative to those treated with conventional chemotherapy regimens. However, the efficacy of treatment with ALK inhibitors in patients with ALK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…Tamiya et al reported a case wherein the patient had a heavy smoking history and did not respond well to alectinib [ 3 ]. However, Mamesaya et al reported an ALK-positive patient with SCC without smoking history who was successfully treated with alectinib [ 4 ], which was similar to our case. These cases implied that smoking status may be a predicting factor for alectinib treatment in ALK-positive patients with SCC.…”
Section: Discussionsupporting
confidence: 86%
“…Tamiya et al reported a case wherein the patient had a heavy smoking history and did not respond well to alectinib [ 3 ]. However, Mamesaya et al reported an ALK-positive patient with SCC without smoking history who was successfully treated with alectinib [ 4 ], which was similar to our case. These cases implied that smoking status may be a predicting factor for alectinib treatment in ALK-positive patients with SCC.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, EGFR and its ligands may have critical roles in ALK-rearranged Sq-LC as an off-target mechanism of alectinib resistance. On the other hand, a case of successful management of ALK-rearranged Sq-LC by initial treatment with alectinib has been reported [ 19 ], although additional cases must be studied in order to determine whether this is a general phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The variants CDKN2A (p.Leu65Pro) and ALK (p.Ile1461Val) were found in another patient also with lung SqCC, with the same variant frequency (data not shown). Somatic alterations of ALK gene are reported relatively rarely in squamous cell carcinoma (SqCC) (48), but, on the other hand, CDKN2A alterations are common and have been reported in FIGURE 4 | Pathogenicity web plotting prediction scores for the three variants, FGFR3 (p.Ser249Cys) (left side), CDKN2A (p.Leu16Profs *9) (middle side), and HRAS (p.Gh161Pro) (right side). Values are scaled so that the most pathogenic scores are plotted toward the external circles.…”
Section: Discussionmentioning
confidence: 99%
“…The variants CDKN2A (p.Leu65Pro) and ALK (p.Ile1461Val) were found in another patient also with lung SqCC, with the same variant frequency (data not shown). Somatic alterations of ALK gene are reported relatively rarely in squamous cell carcinoma (SqCC) ( 48 ), but, on the other hand, CDKN2A alterations are common and have been reported in recent genomic studies of lung SqCC ( 49 ). Interestingly, in one recent study, which included three patients with lung SqCC, the rate of concordance in somatic mutations between local metastasis in distinct lung lymph nodes and primary lung cancer varies from 15 to 82%, and some nodes have highly similar somatic mutation profiles ( 45 ).…”
Section: Discussionmentioning
confidence: 99%